Pengembangan Usaha Mikro D’perez 77 Es Jeruk Sonkit Kiamboi melalui Strategi Promosi - Santi Rimadias; Beatrice Ellena Kurniawan; Dustin Antonio; Euginia Felicia; Fidel Mervin Effendi (Assoeltan: Indonesian Journal of Community Research and Engagement, 2023)
This community service was carried out to increase the visibility and sales of Es Jeruk Sonkit Kiamboi D'perez 77 through promotional strategies. Based on the results of interviews with several customers, it is known that the design of the business booth is less attractive. Therefore, the promotional strategies implemented include: Redesign booth: The booth was redesigned to be more attractive and informative, by adding a clearer logo, tagline, and product information; and Online marketing: Conducted online marketing campaigns through social media and websites, using interesting and informative content. This PKM program uses mentoring or Participatory Action Research (PAR) methods in its implementation. Data collection includes carrying out site surveys and documenting training and discussion materials as well as output results in the form of work products. The training process consists of preliminary, implementation and evaluation stages. The observation and interview methods are used to analyze the market response to the promotional strategies implemented. The results showed that the promotional strategy applied succeeded in increasing product visibility and sales. This can be seen from the increase in the number of booth visitors and the increase in the number of product orders. This devotion provides new insights for business owners in developing more effective business strategies. Business owners can implement similar promotional strategies to increase product visibility and sales.